The Oxford Dictionary of Music / Michael Kennedy, Joyce Bourne Kennedy, Tim Rutherford-Johnson - Kennedy, Michael
This quick reference book of musical terminology includes brief biographical sketches of musicians, composers, vocalists, and conductors.